COMPARISON OF SDS-PAGE PROTEIN PROFILES OF COLORECTAL CANCER TISSUES EXTRACTED USING THREE DIFFERENT EXTRACTION BUFFERS - Chiuan-Herng Leow; Manjit Singh; Boon-Hui Gooi; Che Nin Man; Lay-Harn Gam (Tropical Life Sciences Research, 2008)
Colorectal cancer is one of the major public concerns due to its increasing incidents worldwide. Proteomics approach may serve as a useful tool in understanding the development of the disease. Analysis of protein expression in colorectal cancer and normal tissues will lead to the understanding of the disease that may improve its prognosis. The property of proteins varied dependent on their amino acid composition and folding. Therefore, there is no single extraction buffer possible to extract total proteins from the tissues. In this study, we used three extraction buffers to extract proteins from the homogenized colorectal tissues. The Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) profiles of the buffer extracts show common and distinct proteins extracted in each buffer. Excluding the heterogeneous proteins that migrated as multiple bands in SDS-PAGE, five proteins were identified exclusively in the buffers, namely alpha-1-antitrypsin and haptoglobin precursor in Phosphate (Ph) buffer, smooth muscle cell associated protein-1 (SMAP-1b) and keratin 20 in Lysis (Ly) buffer, and actin-gamma 1 (ACTG1) protein in Thiourea (Thio) buffer. The data indicates that the combination of buffers is needed in the proteomic analysis of colorectal tissues. Kanser usus merupakan satu daripada kebimbangan umum yang utama disebabkan peningkatan insidennya di seluruh dunia. Pendekatan proteomik boleh dijadikan suatu kaedah yang berguna dalam mengenali pembentukan kanser usus. Analisis ekspresi protein dalam tisu kanser usus dan tisu normal usus akan membawa kefahaman terhadap penyakit ini yang seterusnya boleh menambahbaikkan prognosisnya. Sifat setiap protein berbeza bergantung kepada komposisi asid amino dan lipatan protein. Oleh itu, tiada penampan ekstrak tunggal yang boleh mengekstrak kesemua protein. Dalam kajian ini, kami menggunakan tiga penampan ekstrak untuk mengekstrak protein daripada tisu-tisu usus yang dihancurkan. Profil Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) menunjukkan terdapat protein yang sama dan juga berlainan yang diekstrak oleh setiap penampan daripada tisu. Dengan mengecualikan protein heterogen yang bermigrasi kepada beberapa jalur dalam SDS-PAGE, lima protein dikenal pasti secara eksklusif dalam penampan-penampan ekstrak termasuk alfa-1-antitripsin dan pelopor haptoglobin dalam penampan Fosfat (Ph), keratin 20 dan smooth muscle cell associated protein-1 (SMAP-1b) dalam penampan Lysis (Ly), dan actin-gamma 1 (ACTG1) protein dalam penampan Thiourea (Thio). Data-data yang didapati menunjukkan kombinasi penampan-penampan yang diperlukan dalam analisis proteomik bagi kanser usus.